Comparison of students' physics motivation by gender using the Physics Motivation Questionnaire (PMQ): Rasch model analysis - Anisa Widyastuti; Elvine Heranita; Moh. Irma Sukarelawan (Universitas Ahmad Dahlan, 2023)
During the pandemic, many physics teachers only deliver material without adequate learning assistance. This directly or indirectly has influenced students' motivation to learn physics. The analysis of motivation so far has only used the classical test theory approach, so it cannot describe motivation at the individual level. Therefore, this study analyzes students' motivation to learn physics using the Rasch model. This research uses a survey research type. The survey was conducted on 27 class X and XI students who were selected using convenience sampling. The instrument used is the Physics Motivation Questionnaire (PMQ), adapted from the Science Motivation Questionnaire (SQM) developed by Glynn et al. The PMQ uses a 5-point Likert rating scale. Motivation levels were collected online using the Google Forms platform. Motivation level data were analyzed using the Wright map, LVP (Logit Value of Person), and Differential Item Functioning (DIF). The analysis results show that the average level of student motivation is higher than the item difficulty level. Male and female students have the highest motivation on the factor/dimension of Career Motivation. Regarding Gender, male students are more anxious and worried about failing physics exams than girls. Meanwhile, female students were more motivated to study physics better than other students. So, there are differences in the motivation of male and female students. Teachers must insert particular messages for students so they both have positive motivation when studying physics. Students must stay focused on their learning efforts and keep trying to improve their understanding of physics.